2015
DOI: 10.6061/clinics/2015(09)03
|View full text |Cite
|
Sign up to set email alerts
|

The impact of tracheotomy on levels of procalcitonin in patients without sepsis: a prospective study

Abstract: OBJECTIVE:Procalcitonin is a reliable biomarker of infection and sepsis. We aimed to determine whether tracheotomy influences the procalcitonin concentrations in patients without sepsis and assess whether operative duration and procedure affect the peak procalcitonin level.METHODS:A total of 38 non-septic patients who required a tracheotomy underwent either a percutaneous dilatational tracheotomy (n=19) or a surgical tracheotomy (n=19). Procalcitonin levels were measured at the beginning of the tracheotomy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Incidence and absolute levels of increased PCT concentration strongly depend on the type and extent of surgery. Dai et al 11 reported that nonspecific increases in PCT levels are observed after tracheostomy in patients without sepsis. However, tracheostomy in particular is often performed while treating sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Incidence and absolute levels of increased PCT concentration strongly depend on the type and extent of surgery. Dai et al 11 reported that nonspecific increases in PCT levels are observed after tracheostomy in patients without sepsis. However, tracheostomy in particular is often performed while treating sepsis.…”
Section: Discussionmentioning
confidence: 99%